1997
DOI: 10.1139/m97-130
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Rhizobium from root nodules of leguminous trees growing in alkaline soils

Abstract: High temperature, pH, and salt stresses in tropical alkaline soils limit nodulation and dinitrogen fixation by strains of Rhizobium from the root nodules of nitrogen fixing trees (NFTs). This study was conducted to determine the variability among Rhizobium strains isolated from different NFTs in growth response to high temperature, pH, and salt concentrations. Variable response to increases in temperature, pH, and salt concentrations was observed. Rhizobium strain isolated from Albizia lebbek survived at 50 °C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
54
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 108 publications
(59 citation statements)
references
References 19 publications
5
54
0
Order By: Relevance
“…Michiels et al (1994) have reported enhanced cell survival at 50°C when bean nodulating Rhizobium strain CIAT899 cells were first exposed to a temperature of 40 or 45°C. Recently we have reported maximum survival temperature for Rhizobium NB8 from Albizia lebbek to be 50°C (Surange et al, 1997). In our present study, the maximum survival temperature recorded for the five strains at 60°C in YEB for 6 h, to our knowledge, is the highest reported for rhizobia (Table 1).…”
Section: Survival Of Rhizobia At High Temperaturesupporting
confidence: 49%
See 4 more Smart Citations
“…Michiels et al (1994) have reported enhanced cell survival at 50°C when bean nodulating Rhizobium strain CIAT899 cells were first exposed to a temperature of 40 or 45°C. Recently we have reported maximum survival temperature for Rhizobium NB8 from Albizia lebbek to be 50°C (Surange et al, 1997). In our present study, the maximum survival temperature recorded for the five strains at 60°C in YEB for 6 h, to our knowledge, is the highest reported for rhizobia (Table 1).…”
Section: Survival Of Rhizobia At High Temperaturesupporting
confidence: 49%
“…Rhizobium strains were isolated from the root nodules of P. juliflora growing in alkaline soils (pH 8.5 to 11.0) at Banthara Research Station, Lucknow, India. The soil temperature of the sites during summer varied from 48 to 52°C (Surange et al, 1997). Nodules were disinfected, crushed in a small amount of saline (0.85% NaCl), and suspension streaked on yeast extract mannitol (YEM) plates.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations